سوء تقديم مقابـلات رصـف الكـلام في اللغـة الهـدف دراسة تحليلية لضبابية المقابلات في اللغة الهدف تطبيقاً على ستة معاجم لـ أحمد زكي البدوي - إبراهيم, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This piece of research is an attempt to disclose the two-tiered significance of the chosen subject-matter: first, collocations are important to translate and at the same time their translation is not so simple as such. Second, collocations can be badly transplanted into TL text in what is known as MISREPRESENTATION due to the problems that translators may encounter, which if not skillfully handled, will result in disrupting the essence of their equivalents originally intended in the SL text. However, analysis shows us the possibility of subclassifying the problems of misrepresenting TL collocations into major problems relating to accuracy, data restrictions, redundancy, inconsistency and incoherency, and their acceptability; and minor problems relating to printing and spelling, independency, and grammatical shortcomings. This is providing that all of these problems have been discussed with special reference to six chosen miscellaneous dictionaries of Ahmad Zaki Badawi since appropriate and relevant examples could easily be extracted. يأتي هذا البحث محاولةً لتبيان الأهمية ثنائية الجوانب للموضوع المعالَج: أولاً إن رصف أو نظم الكلام موضوع حيوي للترجمة وبالوقت نفسه فإنّ ترجمته ليست بالسهولة المتوقّعة. وثانياً قد يترجَم رصف أو نظم للكلام بشكلٍ سيءٍ إلى النصّ الهدف فيما يُعرف بسوء التقديم أو النقل ومردّ ذلك إلى المشاكل التي قد يواجهها المترجمون والتي تخلص إلى تخريب جوهر مقابلاتها التي يبغي النصّ الأصلي نقلها، فيما لو لم يوظّف المترجمون كفاءاتهم في عملية النقل. حيث أظهر تحليل المشاكل هذه إمكانية تصنيفها إلى مجموعتين: المشاكل الرئيسية وهي مجموعة المشاكل التي تتعلق بالوضوح وحجم المعلومات والتكرار المقيت وضعف الترابط والجزالة بين مركّبات نظم الكلام إلى جانب مدى تقبّل القارئ الهدف لها. والمشاكل الثانوية التي يمكن حصرها في مسألة الأخطاء المطبعية والهجائية المتعددة، والاستقلالية، والجانب القواعدي النحوي. وهذا التحليل برمّته قد اتّخذ من ستة معاجم لـ أحمد زكي البدوي مرتعاً خصباً لينهل منها الأمثلة المناسبة ووثيقة الصّلة بالموضوع.